Pengaruh Kompetensi Dan Skeptisisme Profesional Terhadap Kualitas Audit Dengan Moral Reasoning Sebagai Variabel Moderasi Pada Inspektorat Provinsi Sulawesi Selatan - Hajering; Wahyuni, Nur; Kahfi, Zul (STIM-LPI Makassar, 2025)
This reaserch aims to determine the effect of competency and professional sceptism towards audit quality with moral reasoning as moderating variable in the Inspectorat South Sulawesi Province. The population in this study was the entire number of auditors of the Inspektorat South Sulawesi Province, while the sample in this study was determined using census technique so that the entire population was used as a sample. The study uses primary data in the form of a questionnaire. The data analysis method used is Structural Equation Model (SEM) with Smart PLS 3.0 as a software. The result of the research showed that the variables of competency and skepticism professional had positive and significant influence on the audit quality. This means that more competent the auditor and higher the skepticism professional of the auditor, audit quality will increase. It was also found that moral reasoning strengthening the effect of competency and skepticism professional on audit quality.